Power in a warming world the new global politics of climate change and the remaking of environmental inequality - Ciplet, David; Roberts, J. Timmons; Khan, Mizanur Rahman (The MIT Press, 2015)
"An examination of shifting global power dynamics in climate change politics, and how this affects our ability to achieve equitable and sustainable climate outcomes."-- Publisher's website.